Determining Factors for Smoking Habits and FeNO Levels in Male College Student Smokers - Tadjoedin, Irfan Hasyim; Wibowo, Adityo; Damayanti, Triya (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Smoking remains a pervasive and persistent health issue in Indonesia. Numerous studies have explored the impact of smoking and fractional exhaled nitric oxide (FeNO) levels on college students. However, none have been conducted in Indonesia. With a substantial number of smokers and teenage smokers in the country, there is a critical need to understand the implications of smoking. This study aimed to enhance the comprehension of the motivations behind smoking habits and, consequently, to devise more effective smoking cessation programs. It specifically sought to elucidate the relationship between smoking habits and exhaled nitric oxide (NO) levels among college students and to explore the reasons why students smoke. Methods: This study employed analytical and descriptive cross-sectional approaches. We interviewed 124 participants, 30 of whom were randomly selected for FeNO-level testing. Results: The mean age of the subjects was 20.1 ± 1.54 years. Of these, 48 (38.7%) were enrolled in science and technology programs and 76 (61.3%) in social sciences. The Brinkman index predominantly indicated a mild level of smoking (96.8%), with a moderate level observed in 3.2% of the subjects. The median FeNO level was 12 ppb. According to the Horn questionnaire, the most cited reasons for smoking were pleasure (71%), followed by stress relief (66.1%) and stimulation (38.7%). No significant correlation was found between the Brinkman index and FeNO levels. Conclusion: The primary factors influencing smoking habits among the subjects were stress relief and the pleasure derived from smoking. No correlation was observed between smoking habits and exhaled NO levels.